The coherence of powerful laser diodes and formation of lasing channels - Rzhanov Alexey (EPJ Web of Conferences, 2019)
The effect of the radiation coherence length on the lasing channels lateral dimensions in a planar laser diode with a wide contact is considered. The relationship between the coherence of high-power laser diode radiation, its spectrum and the nonlinear optical properties of the laser resonator active medium is discussed.